A core-shell bismuth-based composite material and its preparation method and application

Through electrospinning technology, Bi2O3 particles are coated in micron-scale carbon balls and heat treatment is performed on inert atmosphere to prepare core-shell bismuth-based composite materials, which solves the problem of limited specific capacity of the anode material of existing lithium-ion batteries and achieves high Specific capacity and good cycle stability electrochemical properties.

CN115763714BActive Publication Date: 2025-02-18NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210577968.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-25
Publication Date
2025-02-18
Estimated Expiration
2042-05-25

AI Technical Summary

Technical Problem

The specific capacity of the existing lithium-ion battery anode material graphite is limited, which limits the development of new energy. As an anode material with high research value, its specific capacity has not yet reached its maximum potential.

Method used

Electrospinning technology is used to coat Bi2O3 particles in micron-scale carbon spheres to form a core-shell-like bismuth-based composite material, and its structure is further improved by inert atmosphere heat treatment.

Benefits of technology

At current densities of 100 mA/g and 500 mA/g, the core-shell bismuth-based composite exhibits high specific capacity and good cycling stability, and the discharge specific capacity can remain stable after a longer cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763714B_ABST
    Figure CN115763714B_ABST
Patent Text Reader

Abstract

The present invention provides a core-shell bismuth-based composite material, wherein the core-shell bismuth-based composite material is 2 O 3 A composite material formed by particles coated in micron-sized carbon spheres. The present invention also provides the use of the core-shell bismuth-based composite material as a negative electrode material for a secondary battery. The shell-like bismuth-based composite material can stabilize its specific capacity at 518 mAh / g after 100 cycles of discharge at a current density of 100 mA / g, and its specific capacity remains at 378 mAh / g after 380 cycles of discharge at a current density of 500 mA / g, while showing excellent stability in the rate performance test. Therefore, the shell-like bismuth-based composite material of the present invention can be used as a negative electrode material for a secondary battery to prepare a secondary battery, so that the prepared secondary battery has the advantages of good cycle stability and low resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and secondary batteries, and in particular relates to a core-shell bismuth-based composite material and a preparation method and application thereof. Background Art

[0002] With the continuous increase in population, energy issues have long become an unavoidable problem in human development. Many scientific researchers are committed to promoting the development of new energy and trying to reduce the excessive use of non-renewable energy. Among them, lithium-ion batteries are a hot topic in research, and the development of new anode materials is the key to the research work.

[0003] At present, graphite materials are commonly used in lithium-ion battery anodes. This material with a theoretical specific capacity of only 372 mAh / g limits the development of this new energy. Ordinary graphite anodes cannot provide sufficient specific capacity for lithium-ion batteries, which leads to the fact that this new energy still cannot replace traditional energy. Therefore, many scholars have carried out a lot of research on various elements according to the periodic table. However, there are very few reports on Bi-based materials. In fact, Bi-based materials are also a kind of anode materials with great research value. Through reasonable structural design, Bi-based composite materials can exhibit excellent electrochemical properties when used as lithium-ion battery anodes. Yin et al. prepared one-dimensional Bi / C nanofibers using electrospinning technology and carbon thermal reaction, and obtained a stable specific capacity of 339.3 mAh / g at a current density of 100 mA / g. Yang et al. successfully prepared Bi@C microspheres with Bi nanoparticles uniformly dispersed in carbon spheres using aerosol spray pyrolysis technology. The specific capacity was 280 mAh / g after 100 cycles at a current density of 100 mA / g. However, there is still room for further improvement in the specific capacity of Bi-based composite materials. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a core-shell bismuth-based composite material, which has a high specific capacity at current densities of 100 mA / g and 500 mA / g, high cycle stability, and can fully exert lithium storage performance.

[0005] To achieve the above object, the present invention adopts the following technical solution.

[0006] A core-shell bismuth-based composite material is a composite material formed by encapsulating Bi2O3 particles in micron-sized carbon spheres.

[0007] In some embodiments, the core-shell bismuth-based composite material is a composite material formed by encapsulating Bi2O3 particles in micron-sized carbon spheres and then subjecting the composite material to heat treatment in an inert atmosphere.

[0008] In some embodiments, the mass percentage of carbon in the core-shell bismuth-based composite material is 70-75%; the mass percentage of Bi is 14-16%.

[0009] In some embodiments, the method for encapsulating Bi2O3 particles in micron-sized carbon spheres is as follows: Bi2O3 particles are added to a spinning solution for electrostatic spinning, thereby encapsulating the Bi2O3 particles in micron-sized carbon spheres.

[0010] In some embodiments, the Bi2O3 particles are prepared by a hydrothermal method.

[0011] In some embodiments, the diameter of the Bi2O3 particles is 150-210 nm.

[0012] In a preferred embodiment, the diameter of the Bi2O3 particles is 170-190 nm.

[0013] In a more preferred embodiment, the diameter of the Bi2O3 particles is 180 nm.

[0014] In some embodiments, the concentration of the Bi2O3 particles in the spinning solution is 8-12 g / L.

[0015] In a preferred embodiment, the concentration of the Bi2O3 particles in the spinning solution is 9-10 g / L.

[0016] In some embodiments, the spinning solution comprises polyacrylonitrile and N,N-dimethylformamide, and the solid-liquid ratio of the two is (70-80):1 g / L; further, the solid-liquid ratio of the two is (75-80):1 g / L.

[0017] In some embodiments, the voltage of the electrospinning is 18-25 KV.

[0018] The present invention also provides the use of the core-shell bismuth-based composite material as a negative electrode material for a secondary battery.

[0019] In some embodiments, the secondary battery is a lithium-ion battery.

[0020] The present invention also provides a method for preparing the core-shell bismuth-based composite material, comprising the following steps: (1) preparing Bi2O3 particles: adding Bi(NO3)3·5H2O and PVP to dilute nitric acid to prepare a solution A; dissolving urea in ethylene glycol to prepare a solution B; mixing the solution B and the solution A evenly, reacting at 100 to 200°C for 1 to 3 hours, washing the product, and obtaining the Bi2O3 particles; (2) adding the Bi2O3 particles to a spinning solution composed of polyacrylonitrile and N,N-dimethylformamide, and encapsulating the Bi2O3 particles in micrometer-sized carbon spheres by electrostatic spinning at a voltage of 18 to 25KV.

[0021] In some embodiments, the preparation method further comprises curing and nitriding the electrospun product: curing the electrospun product in an air atmosphere at 260-280° C., and then nitriding in a nitrogen atmosphere at 600-800° C.

[0022] In a preferred embodiment, the electrospun product is cured at 260-270° C. in an air atmosphere, and then nitrided at 700-800° C. in a nitrogen atmosphere.

[0023] In some embodiments, the molar ratio of Bi(NO3)3·5H2O, PVP, and urea is (0.5-3): (5-10)×10 -3 :(4~8).

[0024] In a preferred embodiment, the molar ratio of Bi(NO3)3·5H2O, PVP, and urea is (1-2): (7-8.5)×10 -3 :(4.5~6.5).

[0025] In some embodiments, the mass ratio of the Bi2O3 particles to polyacrylonitrile is (0.1-0.14): (0.8-1.2).

[0026] In a preferred embodiment, the mass ratio of the Bi2O3 particles to polyacrylonitrile is (0.1-0.12): (0.9-1).

[0027] In some embodiments, the concentration of the Bi2O3 particles in the spinning solution is 8-12 g / L.

[0028] In a preferred embodiment, the concentration of the Bi2O3 particles in the spinning solution is 9-10 g / L.

[0029] In some embodiments, the concentration of the dilute nitric acid is (0.5-2) mol / L.

[0030] The present invention provides a shell-like bismuth-based composite material formed by coating Bi2O3 particles in micron-sized carbon balls by electrostatic spinning. The inventor has found through research that the carbon micron balls are prepared by the electrostatic spinning method to achieve the coating of Bi2O3 particles, which can greatly improve the cycle stability of Bi2O3 particles. The half-cell prepared by the shell-like bismuth-based composite material as the negative electrode material can be stabilized at 518mAh / g after 100 cycles of discharge capacity at a current density of 100mA / g, and the specific capacity remains at 378mAh / g after 380 cycles of discharge at a current density of 500mA / g, and at the same time, it shows excellent stability in the rate performance test. Therefore, the shell-like bismuth-based composite material of the present invention can be used as a secondary battery negative electrode material for preparing a secondary battery, so that the prepared secondary battery has the advantages of good cycle stability and low resistance.

[0031] The present invention firstly prepares Bi2O3 particles by a hydrothermal method. The prepared Bi2O3 particles have the advantage of good molding effect and are very suitable for electrostatic spinning. Then, the Bi2O3 particles are further coated in micron-sized carbon spheres by high-voltage electrospinning technology, and the shell-like bismuth-based composite material is obtained by heat treatment in an inert atmosphere. The preparation method is simple and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart for preparing the shell-like bismuth-based composite material.

[0033] Figure 2 This is a diagram showing the identification results of the shell-like bismuth-based composite material of the present invention; wherein: (a) Bi2O3 particles; (b) Bi@C; (c): XRD spectrum of Bi@C; (d) TEM image; (e) and (f) element mapping images.

[0034] Figure 3 This is a thermal analysis diagram of the shell-like bismuth-based Bi@C composite material of the present invention.

[0035] Figure 4 The performance test results of the shell-shaped bismuth-based Bi@C composite material of the present invention are shown in FIG. 1 ; wherein: (a) Bi@C at 0.1 mV s -1 CV curves at different scan rates; (b) 100mAg -1 Cycling performance at current density; (c) 500mAg -1 Long cycle performance under current density; (d) rate performance of Bi@C; (e) electrochemical impedance spectroscopy; (f) impedance fitting equivalent circuit diagram. DETAILED DESCRIPTION

[0036] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.

[0037] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.

[0039] In the present invention, the term "multiple" refers to two or more than two. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0040] The following describes the invention in conjunction with specific embodiments.

[0041] Example 1

[0042] This embodiment provides a core-shell bismuth-based composite material, which is prepared by the following method:

[0043] (1) First, Bi2O3 particles were prepared by a hydrothermal method: 1.5mmol Bi(NO3)3·5H2O and 7.5μmol PVP were added to 20ml of 1mol / L dilute nitric acid to prepare solution A; 5.4mmol urea was dissolved in 100ml ethylene glycol to prepare solution B; solution B was poured into solution A, the solutions were mixed evenly and then loaded into a 200ml reactor, reacted at 150°C for 3h, and washed with deionized water and ethanol several times to obtain regular and uniform Bi2O3 particles with a diameter of about 180nm;

[0044] (2) 0.12 g of the Bi2O3 particles (concentration 10 g / L) was added to a spinning solution consisting of 0.9 g of polyacrylonitrile (PAN) and 12 ml of N,N-dimethylformamide (DMF) (PAN concentration was 75 g / L), and micron carbon spheres were prepared by high-voltage electrospinning at a voltage of 25 KV, in which the Bi2O3 particles were coated; the electrospun matrix prepared by the PAN-DMF electrospinning system was cured in an air atmosphere at 260°C, and the DMF solvent was removed at the same time; the cured PAN electrospun matrix was nitrided in a nitrogen atmosphere at 700°C to prepare a stable nitrogen-doped carbon matrix, and finally the core-shell bismuth-based composite material (named Bi@C composite material) was obtained.

[0045] like Figure 2 As shown, the Bi2O3 composite material prepared by hydrothermal method was observed by SEM ( Figure 2 a), the spheres with a diameter of about 180 nm have good forming effect and are suitable for further processing and research. The morphology of the Bi@C composite material is shown in FIG. Figure 2 As shown in (b), it presents a micron-sphere structure connected by fiber filaments. The most important thing is that these micron-carbon spheres are coated with a large number of Bi particles, which can be Figure 2 The XRD pattern of Bi@C in (c) is confirmed by the perfect match with the Bi standard card PDF#44-1246, which proves that a large number of Bi particles should have been encapsulated in the carbon microspheres.

[0046] Figure 2 The TEM image in (d) proves this point more intuitively. Under high brightness display, the carbon microspheres appear gray. Figure 2 In (d and e), the presence of Bi particles is clearly seen, and they appear black. Figure 2 (e) The Bi@C microspheres shown in the figure are used to make a surface scan energy spectrum of each element. Figure 2 f), the distribution of element carbon is clearly presented as a sphere with a diameter of about 2.5 μm, and the distribution of element bismuth is similar to Figure 2 The positions of the black nanospheres in (e) are exactly the same. After the above series of analyses, the successful preparation of the Bi@C composite material can be confirmed.

[0047] Figure 3 The thermal analysis diagram in describes the thermogravimetric analysis of the Bi@C composite material in air atmosphere with a heating rate of 10°C / min. It can be seen that the carbon material content is 71.08%. According to the calculation (Bi%=2Bi / Bi2O3×15.92%), the Bi content in the Bi@C composite material is 14.28%.

[0048] Example 2

[0049] The core-shell bismuth-based composite material prepared in Example 1 was assembled into a CR2032 half-cell and the performance was tested.

[0050] CR2032 type half-cell assembly: Preparation of negative electrode sheet: The Bi@C composite material, acetylene black and binder (PVDF) described in Example 1 are fully mixed in a ratio of 7:1.5:1.5wt%, and then an appropriate amount of N-methylpyrrolidone (NMP) is added and stirred to form a slurry, which is evenly coated on a copper foil. The coated electrode sheet is placed in a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet. The dried negative electrode sheet is pressed and punched, and a CR2032 type half-cell is assembled in a glove box filled with argon. The CR2032 type half-cell consists of the negative electrode sheet, the counter electrode (lithium foil), the separator (Celgard 2400 polypropylene film) and the electrolyte (the electrolyte consists of ethylene carbonate, dimethyl carbonate, diethyl carbonate and LiPF6, and the volume ratio of ethylene carbonate, dimethyl carbonate and diethyl carbonate is 1:1:1; the concentration of LiPF6 is 1M LiPF6).

[0051] The performance of the half-cell was tested, and the half-cell prepared by the Bi2O3 particles of Example 1 (prepared in the same manner as above, except that the Bi@C composite material was replaced by Bi2O3 particles) was used as a control: the test of cycle performance and rate performance was completed on the Land CT2001A charge and discharge instrument produced by Wuhan Landian Electronic Instrument Co., Ltd., and the test voltage was selected from 0.01V to 3.0V. The rate performance test was carried out at five different current densities of 100mA / g, 200mA / g, 500mA / g, 1000mA / g and 100mA / g, and each current density was cycled 10 times. The charge and discharge cycle was cycled 100 times at a current density of 100mA / g, and 380 times at a current density of 500mA / g. The cyclic voltammetry (CV) scan rate was 0.1 mV / s, and the voltage range was 0.01 V to 3.0 V. The test frequency range of electrochemical impedance spectroscopy (EIS) was 0.1 Hz to 100 kHz. The cyclic voltammetry and electrochemical impedance spectroscopy tests were completed on a PGSTAT204 electrochemical workstation produced by Swiss Metrohm Co., Ltd. The equivalent circuit diagram was simulated using software based on the electrochemical impedance spectrum. All experiments were completed at room temperature.

[0052] The test results are as follows Figure 4 shown. Figure 4 The CV curve of (a) reflects the redox reaction of the Bi@C composite material during the cycle. The lower half of the curve shows the process from 3V to 0V. The downward peak represents the reduction reaction of the anode material during the discharge process, that is, Bi 3+ Xiang Bi 0During the first discharge, an obvious reduction peak appears at 0.39V, but it no longer appears in subsequent cycles. This is because a stable SEI film is formed on the anode material after the first cycle. The upper curve represents the charging process. The oxidation peak at 0.92V is due to the occurrence of Bi 0 Xiang Bi 3+ After the SEI film is formed, the second and third cycle curves have a high overlap, indicating that the Bi@C composite material has good cycle stability.

[0053] Figure 4 (b) and Figure 4 (c) The cycling performance of the Bi@C composite material and the Bi2O3 particles prepared in Example 1 at current densities of 100mA / g and 500mA / g, respectively, is compared. It can be clearly seen from the two figures that the Bi2O3 particles have a high initial discharge specific capacity, but the specific capacity decays rapidly during the later cycles, leaving only 32mAh / g and 20mAh / g, respectively. The Bi@C composite material of the present invention greatly improves the problem of severe attenuation of the specific capacity of Bi2O3 particles in the later stages of the cycle. The discharge specific capacity of the Bi@C composite material can be stabilized at 518 and 378mAh / g, respectively, at current densities of 100 and 500mA / g. This is because the presence of carbon microspheres limits the volume expansion of Bi particles during the insertion and extraction of lithium ions. The stable structure of the composite material ensures the stability of the electrochemical cycle.

[0054] cause Figure 4 (b) and Figure 4 The reason for the low first coulombic efficiency in (c) is the formation of SEI film, which is a very common phenomenon in the research of anode materials. After the SEI film is stably formed, the discharge specific capacity can be stabilized at a high level, which is a manifestation of the excellent electrochemical performance of the anode material. Figure 4 This was further verified in the rate performance test of (d). At current densities of 100mA / g, 200mA / g, 500mA / g and 1000mA / g, the discharge specific capacity was stabilized at 518mAh / g, 473mAh / g, 406mAh / g and 352mAh / g, respectively. Moreover, when the current density returned to 100mA / g, its specific capacity could also be stably restored to 518mAh / g. Figure 3 (e) The outline of the Nyquist plot consists of a semicircle (high frequency region) and an inclined straight line (low frequency region). Figure 4 The equivalent circuit in (f) fits the experimental data and obtains a charge transfer resistance (Rct) of 132.6Ω. Low resistance is also one of the reasons for the excellent electrochemical performance.

[0055] In summary, the present invention creatively adopts a high-voltage electrospinning method to prepare carbon microspheres, realizes the coating of Bi2O3 particles, and becomes Bi@C after heat treatment in an inert atmosphere, which greatly improves the cycle stability of Bi particles. The prepared Bi@C composite material can stabilize the specific capacity of 518mAh / g after 100 cycles of discharge at a current density of 100mA / g, and the specific capacity of 378mAh / g after 380 cycles of discharge at a current density of 500mA / g, and also shows excellent stability in the rate performance test.

[0056] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a core-shell bismuth-based composite material, characterized in that: The method comprises the following steps: (1) preparing Bi2O3 particles: adding Bi(NO3)3·5H2O and PVP into dilute nitric acid to prepare solution A; dissolving urea into ethylene glycol to prepare solution B; mixing solution B and solution A evenly, reacting at 100-200°C for 1-3h, washing the product, and obtaining the Bi2O3 particles; (2) adding the Bi2O3 particles into a spinning solution composed of polyacrylonitrile and N,N-dimethylformamide, and encapsulating the Bi2O3 particles in micrometer-sized carbon spheres by electrostatic spinning at a voltage of 18-25KV; The electrospun product was cured in an air atmosphere at 260-280°C and then nitrided in a nitrogen atmosphere at 600-800°C; The mass ratio of the Bi2O3 particles to polyacrylonitrile is (0.1-0.14): (0.8-1.2).

2. The method for preparing the core-shell bismuth-based composite material according to claim 1, characterized in that: The molar ratio of Bi(NO3)3·5H2O, PVP, and urea is (0.5-3): (5-10)×10 -3 :(4~8).

3. A core-shell bismuth-based composite material prepared by the method for preparing a core-shell bismuth-based composite material according to any one of claims 1 to 2, characterized in that: The core-shell bismuth-based composite material is a composite material formed by encapsulating Bi2O3 particles in micron-sized carbon spheres.

4. The core-shell bismuth-based composite material according to claim 1, characterized in that: The core-shell bismuth-based composite material is a composite material formed by encapsulating Bi2O3 particles in micrometer-sized carbon spheres and then subjecting the composite material to heat treatment in an inert atmosphere.

5. The core-shell bismuth-based composite material according to claim 3 or 4, characterized in that: The mass percentage of carbon in the core-shell bismuth-based composite material is 70-75%; the mass percentage of Bi is 14-16%.

6. The core-shell bismuth-based composite material according to claim 3 or 4, characterized in that: The method for encapsulating Bi2O3 particles in micron-sized carbon spheres is as follows: Bi2O3 particles are added to a spinning solution for electrostatic spinning, thereby encapsulating the Bi2O3 particles in micron-sized carbon spheres.

7. The core-shell bismuth-based composite material according to claim 6, characterized in that: The diameter of the Bi2O3 particles is 150-210 nm; and / or the concentration of the Bi2O3 particles in the spinning solution is 8-12 g / L.

8. The core-shell bismuth-based composite material according to claim 6, characterized in that: The spinning solution comprises polyacrylonitrile and N,N-dimethylformamide, and the material-liquid ratio of the two is (70-80):1 g / L.

9. Use of the core-shell bismuth-based composite material as claimed in any one of claims 3 to 8 as a negative electrode material for a secondary battery.

Citation Information

Patent Citations

  • Alpha-Bi2O3 loaded carbon material supercapacitor electrode material and preparation method thereof

    CN111554519A

  • Bismuth-based nano material as well as preparation method and application thereof

    CN113161530A